Adsorption and sugarcane-bagasse-derived activated carbon-based mitigation of 1-[2-(2-chloroethoxy)phenyl]sulfonyl-3-(4-methoxy-6-methyl-1,3,5-triazin-2-yl) urea-contaminated soils - Ahmad Khuram Shahzad (Open Chemistry, 2020)
Burgeoning pesticide usage in agriculture sector required to be evaluated by assessing the adsorption rate in soils. The herbicide triasulfuron was used in this research to analyze its sorption behavior in seven distinct soils using batch equilibrium methodology. The adsorption coefficient (Kd) values ranged from the 3.32 to 29.7 µg/mL. Peshawar soil displayed the highest Kd value because of the distinct physiochemical properties when compared with the other six samples. Gibbs free energy exhibited negative values displaying less contact between soil particles and pesticides, showing the exothermic nature of the phenomena. A negative association was observed between the pH of the soil samples and Kd (R2 = −0.71) but a direct relation with the organic content (R2 = 0.74). Triasulfuron mitigation was performed by the economical remediation of soils using acid-activated charcoal prepped from Saccharum officinarum husk. Activated carbon derived from biomass displayed the great potential for triasulfuron removal from soils.